Noel Desmond Stockton (born 1930): arranger, composer and pedagogue - Potgieter, Johannes Joubert (University of the Free State, 2000)
The idea of a study on this subject was born out of the realisation that in recording the history of music, many omissions occur in regard to musicians and pedagogues who made important contributions to the music profession. After some informal investigation in the form of interviews, formal research on this dissertation commenced in 1999 and the study was completed in December 2000.. The main aim of the study was to highlight Stockton's contribution to music in South Africa, as one of the country's foremost Jazz artists, as well as a highly prolific arranger, composer and pedagogue. The study is divided into the following sub-sections: Chapter 1 This introductory chapter deals with the research design and research methodology. It also states the aims of the study as well as the necessity thereof. Chapter 2 A biographical study on his life and activities, from professional pianist as a sixteen year old to lecturer in Jazz at the University of the Orange Free State. Insight regarding his development as an artist and pedagogue is the main thread throughout this section. After chapter two the text is supported by visual documentation in the form of photographs. Chapter 3 Here Stockton is dealt with as lecturer. His approach towards Jazz tuition, the problems he came across during his years of teaching these and his suggestions on the teaching of various courses are presented in a concise, but meaningful way. Former students' views on his tuition support this chapter. The chapter also deals with the compilation of a Jazz course on tertiary level. This section ends with a general discussion of Jazz tuition and Jazz style, constructed on Stockton's own views on these issues. Chapter 4 This chapter commences with discussions of Stockton's five serious compositions and concludes with discussions on a selection of the bigger arrangements for full symphony orchestra. Seen against the background that Stockton wrote hundreds of arrangements, discussions on the complete repertoire of these was not feasible. The analysis have been performed in a systematic annotated way. Chapter 5 This chapter contains the conclusions of the study as well as a recommendation on the importance of music history writing on contemporary, lesser known composers and musicians who made enormous contributions to the music scene. In the appendixes (a) a work Iist is provided, as well as the (b) scores of the eight compositions/arrangements discussed in chapter four. The study concludes with (c) sound documentation of the serious compositions on the first compact disc and a selection of arrangements by Stockton on the second.
Dissertation (M.Mus. (Music))--University of the Free State, 2000
Keywords: Composers -- Biography; Jazz -- History and criticism; Arrangement (Music)